Implementasi Etika Profesi sebagai Upaya Pencegahan Penyalahgunaan Dana dalam Manajemen Keuangan - Anugrah Mardiah Putri; Dito Aditia Darma Nst; Dinda Widayanti; Lutfiah Adinda Azahara; Juli Arti Waruwu; Lastri Silaban; Yesi Rahmawati (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2025)
Financial management, both in public and private organizations, is highly vulnerable to fraud and misappropriation of funds. The risk of fraud in financial reporting not only jeopardizes an organization's long-term financial health but also damages the reputation and trust of stakeholders. Professional ethics and integrity are key factors in ensuring good, efficient, and effective financial governance. Weak internalization of professional ethical values ​​among financial practitioners, such as manipulation of financial reports and unauthorized use of official funds, is often a major cause of misappropriation of funds. These cases can significantly harm an organization, as seen in violations of codes of ethics in various large companies. Therefore, strengthening professional ethics in financial management practices is crucial to prevent misappropriation of funds, fraud, or financial manipulation. A strong internal control system, coupled with a good ethical culture, can play a significant role in preventing and detecting these conditions. This study aims to identify factors that support and hinder the implementation of professional ethics in financial management and provide recommendations for improving integrity and accountability in fund management. It is hoped that the results of this study will help organizations strengthen governance, increase transparency, and reduce the risk of fraud through better implementation of professional ethics.